PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY (TS-TS) TERHADAP HASIL BELAJAR MAHASISWA EKONOMI UNIVERSITAS MUHAMMADIYAH METRO - Siti Suprihatin (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Education is a very important element for creating quality, intelligent, peaceful, open, democratic, and able to compete and can improve the welfare of all Indonesian citizens. The state is said to be progressing in all fields both in the fields of economics, technology, agriculture or the other not apart from the role of education. The purpose of this research is to find out the Effect of Two Stay Two Stray Type of Cooperative Learning Model on Student Education Results of Economic Education at Muhammadiyah Metro University. The usefulness is to know the Effect of Cooperative Learning Model Type Two Stay Two Stray (TS-TS) on Student Learning Outcomes of economic education students